The Shelter Characteristics of Traditional-styled Inuit Snow Houses - Kershaw, G. Peter; Scott, Peter A.; Welch, Harold E. (ARCTIC, 1996)
The shelter value of snow iglus at Resolute (74 41 N, 94 54 W) in the Canadian High Arctic was assessed. After a survey of snow conditions, construction sites were chosen and two iglus were built and furnished in a traditional way. A large iglu (4.1 m diameter) contained 72 blocks averaging 23.6 kg and had a surface area-to-volume ratio of 2.21:1. A smaller iglu (3.05 m in diameter) contained 46 blocks averaging 28.2 kg and had a surface area-to-volume ratio of 1.73:1. The smaller iglu provided 75% of the large iglu's space for 76.5% of its mass. Snow hardness averaged 12000 g/sq. cm, and the mean density of the snow was 397 kg per cu m. The energy required to build and heat each iglu was calculated from the snow characteristics, construction activities and microclimate parameters measured during occupancy. Heat flux was calculated for human bodies, kudliks (seal oil lamps), and geothermal sources at temperature differentials as high as 45 C from ambient, for both the unlined large iglu and the small iglu, which was lined with caribou skins on the inside. The smaller iglu was more efficient, requiring the fat of one seal every 6.3 days for heating, while the large iglu required the fat of one seal every 3.7 days. The meat content of each seal would have sustained a family of four for the same time interval, and the resultant body heat would have provided 8% to 14% of the total energy necessary to maintain comfortable temperatures within the iglu. On a évalué la valeur de la protection offerte par les igloos de neige à Resolute (74° 40' de latit. N.) dans l'Extrême-Arctique canadien. On a d'abord procédé à un relevé de l'état de la neige, puis choisi les sites et construit et équipé deux igloos de façon traditionnelle. Soixante-douze blocs de neige pesant en moyenne 23,6 kg ont servi à construire le grand igloo (4,1 m de diamètre) dont le rapport surface:volume était égal à 2,21. Quarante-six blocs pesant en moyenne 28,2 kg ont servi à la construction du petit igloo dont le rapport surface:volume était égal à ...